Proactive Approach to Manufacturing Planning - Peter Bubeník; Filip Horák (Kvalita Inovácia Prosperita, 2014)
Proposed concept of proactive manufacturing planning uses sets of knowledge to create plan. These sets of knowledge are gained from transformation of historical data of selected indicators. This concept uses the analysis of occurred events, which is done by applying data mining methods to known historical data. Results of analysis are then recorded into knowledge-based system for further use. Application of data mining techniques helps to find hidden relationships with high influence on final decision of planner. This concept aims to navigate planner during creation of real plans resulting from real situations. Unknown situations are modelled using simulation module.